009 Normobaric hypoxia impairs cardiac energetics and diastolic function in normal human volunteers. (22nd September 2015) - Holloway, C J; Cochlin, L E; Codreanu, Ion; Bloch, E; Fatemian, M; Johnson, A; Robbins, P; Nuebauer, S; Clarke, K
Abstract : Background: Left ventricular dysfunction is consistently observed in human heart in the first few days of hypoxic exposure, yet the cellular mechanisms underlying the dysfunction are poorly understood. We postulated that normobaric hypoxia impairs cardiac energetics leading to cardiac dysfunction. Healthy males (n=12, age 24±2) underwent 20 h of normobaric hypoxia in purpose-built hypoxia chambers. The partial pressure of oxygen during end tidal expiration (PETO2) was kept between 50 and 60 mmHg, whilst keeping peripheral oxygen saturation (SaO2) above 80%. Cardiac function was measured using magnetic resonance imaging (MRI) and echocardiography before and after hypoxic exposure. High energy phosphate metabolism was measured as the ratio of phosphocreatine to ATP (PCr/ATP) using 31Phosphorus magnetic resonance spectroscopy (MRS) before and after 20 h of hypoxia. During hypoxia, PETO2 and SaO2 averaged 55±1 mmHg and 83.6±0.4%, respectively. There was a 15% reduction in cardiac PCr/ATP, from 2.0±0.1 before to 1.7±0.1 after hypoxia (p<0.01), and reduced diastolic function, measured as E/E', from 6.1±0.4 to 7.5±0.7, (p<0.01). Short term normobaric hypoxia led to rapid changes in cardiac energy metabolism and alterations in diastolic function in normal human hearts. Increased cardiac energy demand and reduced oxygen-limited decrease in oxidative phosphorylation may explain the low PCr/ATP and cardiac dysfunction observed after hypoxic exposure, whether in health or disease.